Cádmio, cobre e cromo em solo e plantas de milho após quinze anos de aplicações anuais de lodo de esgoto - Reis, Iolanda Maria Soares [UNESP] (2014)
Sewage sludge, a residue of diverse constitution and high levels of essential elements plants, can increase the levels of soil organic matter and its utilization in agriculture one of the alternatives more viable nutrient cycling. However, problems such as heavy metals are constant for application of sewage sludge in agriculture barriers. The objectives of this study were to evaluate the adsorption of cadmium, copper and chromium in soil samples originating from the field experiment, installed fifteen years ago, with annual applications of doses of sewage sludge; evaluate the available contents of these elements and pseudototals levels in soil, plants and grains of corn. In this sense, was installed in field conditions, in randomized blocks in an Oxisol subjected to four treatments: 0, 5, 10 and 20 Mg ha-1 of sewage sludge, dry basis in five blocks. The behavior of cadmium, copper and chromium were investigated in soil samples through pseudototals levels, adsorbed available and associated organic matter fractions and the vegetable samples, we analyzed the levels of diagnostic leaf, whole plant (except root ) and grain corn and grain. Langmuir isotherm and Freundlich were constructed to estimate the adsorption parameters. In general, it was observed that the maximum adsorption capacity of cadmium, copper and chromium were not changed with the doses of sewage sludge as well as pseudototais and available content, and pseudototals levels in association with organic matter fractions, have not demonstrated a direct influence of the doses of sewage sludge. The fertilization with sewage sludge supplemented with K was as effective as mineral fertilizer for grain yield of maize